Replacement of Monensin with a Proprietary Tannin-Blend Additive in Calf-Fed Holstein Steer Diets - Sydney M. Bowman-Schnug; Luke K. Fuerniss; Joe D. Cameron; Jonathon L. Beckett; Muhammad Ahsin; Stephan van Vliet; Guy D. Hufstedler; Bradley J. Johnson (Veterinary Sciences)
The discussion of antimicrobial resistance has begun to impact consumer preference and influence the implementation of certain growth-promoting technologies in the cattle feeding industry [...]